Handheld infrared camera use for suicide bomb detection: feasibility of use for thermal model comparison - Dickson, Matthew R (Kansas State University, 2008)
One of the most deadly tactics used by today’s terrorists is suicide bombing. Sensors have been developed and are being used in different situations to detect weapons and the people initiating suicide bombing attacks. The ideal detection technology would be fast, accurate, effective from long distances, and safe for the both detector and the object being detected. One detector that has shown potential as a tool for detecting hidden weapons is an infrared detector. Infrared detectors are passive sensors that create infrared, or thermal, images without having to expose the subject to any radiation. These images show the heat signature that is given off by objects of interest. Previous studies using infrared detectors for concealed weapon detection have tried to observe the image of the weapon. These have been largely unsuccessful, however, because infrared waves will not readily penetrate clothing. The research presented here determines the feasibility of modeling the heat signature produced by a suicide bomber using thermal models that predict the temperature of the exterior layers of clothing worn. The goal is to be able to compare the images acquired of the suspected bomber to the expected temperatures from the thermal models. If the presence of a hidden weapon affects the emitted heat signature to a point in which the clothing temperatures are not responding as predicted by a model, it is possible a detection system may be created using these models as a comparator and signal for detection. This research also determines a temperature range for which an operator viewing infrared images for suicide bomb detection may be relatively certain of the presence of a foreign object. Testing was also completed to determine those variables that affect an infrared image in ways that help or hinder the use of the thermal models in predicting the temperatures that appear in the infrared images.
Keywords: Suicide bomb; Infrared; Engineering, Mechanical (0548)